2018
DOI: 10.1149/2.0841803jes
|View full text |Cite
|
Sign up to set email alerts
|

Duty Cycle Effects on the Step Potential Electrochemical Spectroscopy (SPECS) Analysis of the Aqueous Manganese Dioxide Electrode

Abstract: Step potential electrochemical spectroscopy (SPECS) has previously been demonstrated as an effective method for deconvoluting charge storage processes in electrochemical capacitor materials. Herewith is described the effect of the two main experimental variables in SPECS; namely the potential step size and the electrode rest time, on the behavior of the aqueous manganese dioxide electrode. The potential step size dictates polarization at the electrode-electrolyte interface, and hence the driving force for char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Note that the linearity of the graph increases with increasing the amount of added carbon material, indicating a more ideal behavior and reduction in the Ohmic drop. 15 The results (Figure 6c) showed that increasing the scan rate resulted in a decrease in the percentage of the diffusion current. Also, upon increasing the percentage of added carbon material, the percentage of the diffusion current is greatly reduced.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that the linearity of the graph increases with increasing the amount of added carbon material, indicating a more ideal behavior and reduction in the Ohmic drop. 15 The results (Figure 6c) showed that increasing the scan rate resulted in a decrease in the percentage of the diffusion current. Also, upon increasing the percentage of added carbon material, the percentage of the diffusion current is greatly reduced.…”
Section: Resultsmentioning
confidence: 93%
“…All tested materials resulted in b values (the intercept of the log i vs log v plot) that are ∼0.6, indicating the predominance of the diffusion charge storage mechanism. 14,15 Moreover, using Trasatti’s method, 16 the total capacitance (EDL and the diffusion) was calculated. It is worth mentioning that because of the used neutral electrolyte and the high scan rate, the relations were not entirely linear.…”
Section: Resultsmentioning
confidence: 99%
“…The dramatic decrease in the geometric capacitive current at higher potentials could be an indication of the shortage of ions in the electrolyte to occupy all pores of the inner surface areas. This is in contrast with the synthetic voltammogram of capacitive processes for small cells in which there is an abundant of ions in electrolyte [43,44,49]. The diffusional and residual processes have a negligible contribution at the relative sweep rate of 25 mV.s -1 .…”
Section: Synthetic Voltammetrymentioning
confidence: 72%
“…Moreover, it allows separation of charge storage mechanisms, such as electrical double layer and diffusion-limited processes [41,42]. This technique has the potential to characterise the kinetic behaviour of the electrochemical cell over a full range of sweep rates [43] and also to provide additional information about the existence of the residual current such as leakage and self-discharge current, the stability of electrode materials, the ionic mobility of various electrolyte species, the equivalent series resistance of the electrode materials and the effectiveness of the engineering of the device [44][45][46]. The SPECS method has also been used for deconvoluting different charge storage mechanisms such as capacitive and diffusional processes in electrochemical energy storage technologies [43].…”
Section: Introductionmentioning
confidence: 99%
“…32 A number of analysis methods have been devised including examining (i) the current flowing as a function of sweep rate from a series of cyclic voltammetry experiments; 33 (ii) the charge passed during a series of cyclic voltammetry experiments at different sweep rates; [34][35][36] and (iii) step potential electrochemical spectroscopy (SPECS), which is based on analysis of the i-t transients arising from a series of small potential steps across the full potential window. [37][38][39][40][41][42][43][44] In a recent publication from our laboratory we made a comparison between these three methods to examine their ability to differentiate the various charge storage mechanisms. 32 The outcomes from this work demonstrated that the use of the electrode charge method 34 did not adequately describe electrode behavior and thus it has not been considered any further.…”
mentioning
confidence: 99%